New teaching and learning experience with mixed reality technologies. (10th December 2008) - Liu, Wei; Cheok, Adrian David; Mei-Ling, Charissa Kim; Theng, Yin-Leng
Current technologies, especially digital media have developed very fast in the last ten years, bringing changes to our lives and presents new challenges, opportunities and new requirements which are different from conventional delivery modes in education. Mixed reality (MR) technologies, with the features of immersive and tangible interaction, have been explored in education, which provide a more 'engaging' experience to learners. In this article, we will introduce a MR classroom developed for a local primary school in Singapore that includes two modules – solar system and plant system, and a MR exhibition about evolution, which was a public exhibition in the Singapore Science Centre. This novel, interesting learning experience is provided by combining tangible interactions and MR technologies. To identify and address usability and usefulness issues, a study on our MR classroom was conducted. Participants were surveyed on their perceptions towards the MR classroom systems. Preliminary results seemed to indicate participants' intention to use MR for learning, and it was influenced directly by perceived usefulness, and indirectly through perceived ease of use and social influence.